PEMBERDAYAAN MASYARAKAT MELALUI PEMANFAATAN LIMBAH SAMPAH RUMAH TANGGA: KAJIAN PADA BANK SAMPAH DI KABUPATEN SUKOHARJO - Aris Eddy Sarwono, Y Anni Aryani, Doddy Setiawan, Isna Putri Rahmawati & (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2018)
This our team is performed in the garbage bank in Joho, Sukoharjo. The purpose of this devotion activity is to empower the community by utilizing household waste both organic and non organic waste. The result this activity to provide solutions of problems faced by the partners (Joho Makmur and Suka Maju), the management of the handling and waste management, the use of organic and non-organic, management support facilities for waste management, packaging and marketing of bank the waste activities product. This activity is expected to develop the waste bank with local government support.Keywords: Bank waste, organic, non organic, empowerment